2012
DOI: 10.1590/s1677-55382012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Can the delivery method influence lower urinary tract symptoms triggered by the first pregnancy?

Abstract: (2), persisting after delivery in 6% to 29% of women (3). Estimating the post-partum prevalence of urinary incontinence is complex because the prevalence may depend upon the number of previous births, type of delivery, and history of previous inVol. 38 (2): 267-276; March -April, 2012 Introduction and Objectives: The increase of the intensity of urinary symptoms in late pregnancy and postpartum has been well documented by several authors, but their causes remain uncertain, partly because of its probable mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
4
14
0
Order By: Relevance
“…In the present study, the majority of the women had babies weighing more than 3,000g (1,25,30) . Many complications can be reduced or prevented with appropriate obstetric care, but in Brazil, and especially in the region of São José do Rio Preto, obstetric care is exceedingly interventionist, technocratic, medicalized and hospitalcentric, resulting in owning the dishonorable title of being the world champion of caesarean sections.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…In the present study, the majority of the women had babies weighing more than 3,000g (1,25,30) . Many complications can be reduced or prevented with appropriate obstetric care, but in Brazil, and especially in the region of São José do Rio Preto, obstetric care is exceedingly interventionist, technocratic, medicalized and hospitalcentric, resulting in owning the dishonorable title of being the world champion of caesarean sections.…”
Section: Discussionmentioning
confidence: 47%
“…This is a lower proportion than that found in the literature which reveals that lifestyle may have had an influence and that protective measures against the appearance of UI may have been employed even before being pregnant (23)(24) . A relationship between UI in pregnancy and weight gain of pregnant women has been reported as a risk factor for pelvic floor muscle dysfunction (25) . A postpartum strategy for UI prevention is pelvic floor muscle training and postpartum weight loss (26) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, episodes of urine leakage are infrequent and the amount of urine leakage is small (3)(4)(7)(8)(9)(10) . Maternal age greater than 35 years, UI during pregnancy, elevated body mass index (BMI), multiparity, and normal birth are considered risk factors for postpartum UI (4,7,(9)(10)(11)(12)(13)(14) . A 10-year cohort study developed with the goal of assessing the effect of the first normal birth on urinary symptoms showed that it was associated with an increase in SUI, in addition to UUI, regardless of maternal age or number of births (14) .…”
Section: Introductionmentioning
confidence: 99%